2009
DOI: 10.1063/1.3095545
|View full text |Cite
|
Sign up to set email alerts
|

An experimental setup to study the expansion dynamics of laser blow-off plasma plume in variable transverse magnetic field

Abstract: In the present work we report generation of uniform and variable pulsed magnetic field in synchronization with pulsed plasma for the study of the expansion dynamics of laser blow-off (LBO) plasma plume. The experimental procedure for optimizing various parameters of the setup, e.g., the production of pulsed field and its synchronization with pulsed plasma and diagnostics system, is also reported. Until now the effect of magnetic field was studied using fixed field. The present setup, however, provides variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The formation and expansion dynamics of LBO plume are discussed in detail in Refs. [8][9][10]. Earlier studies based on emission spectroscopy have revealed the effects of ambient gas on LBO plume, without any details regarding the structure formation, size, and shape of the plume in various ambient environments.…”
Section: Fast Imaging Of Laser-blow-off Plume: Lateral Confinement Inmentioning
confidence: 96%
See 1 more Smart Citation
“…The formation and expansion dynamics of LBO plume are discussed in detail in Refs. [8][9][10]. Earlier studies based on emission spectroscopy have revealed the effects of ambient gas on LBO plume, without any details regarding the structure formation, size, and shape of the plume in various ambient environments.…”
Section: Fast Imaging Of Laser-blow-off Plume: Lateral Confinement Inmentioning
confidence: 96%
“…8,14 The plasma is viewed through a quartz window mounted orthogonal to the direction of plume expansion. The time resolved images have been recorded by an ICCD camera having variable gain, gate time, and spectral response in 350-750 nm region.…”
Section: Fast Imaging Of Laser-blow-off Plume: Lateral Confinement Inmentioning
confidence: 99%
“…The present experimental setup for double pulse laser ablation consists of five main sub-systems-(i) laser systems, (ii) vacuum system associated with the sample target, (iii) diagnostics system, (iv) pulsed power system and (v) timing synchronization module. A detailed description of the experimental set up can be found elsewhere [5,11]. The plasma plume is generated inside a stainless steel chamber evacuated to a base pressure of ∼ 5x10 −5 Torr.…”
Section: Experimental Schemementioning
confidence: 99%
“…It provides details of the physical mechanism behind the increase in emission intensity for LIBS application. Moreover, different diagnostics systems, e.g., optical emission spectroscopy, a fast imaging spectrograph and electrical probes are used to detect the optical as well as electrical signals from the expanding plasma [5]. The simultaneous use of these diagnostics gives complementary information about the plume dynamics [6] and interpretation of these data provides quantitative information of plasma parameters and fundamental…”
Section: Introductionmentioning
confidence: 99%
“…Further isotropic graphite is favourable material as a target in laser ion source [23]. Detailed description of the experimental setup has been reported in elsewhere [22,24].A brief summary which is important for the present report is summarized here. The plasma plume is created in a vacuum chamber having a base pressure less than 10 -6 Torr using an 1064 nm, 8 ns FWHM pulsed Nd:YAG laser.…”
Section: Introductionmentioning
confidence: 99%